Network Pharmacology and Component Analysis Integrated Study to Uncovers the Molecular Mechanisms of Lansium parasiticum Bark Extract in Colon Cancer Treatment - Mutiah, Roihatul; Briliana, Malich Septi Diajeng; Ahmad, Ananda Rizkia Azizah; Fauziyah, Begum; Janaloka, Nandana Adyuta; Suryadinata, Arief (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
Side effects and risk of resistance are common consequences of colon cancer treatment based on chemotherapy. The medicinal plant originating in Indonesia, Lansium parasiticum bark extract (LPBE), has not been studied much. The purpose of this study is to identify the compounds present in LPBE and explain how the molecular mechanisms of the composite inhibit colon cancer cells. LC-MS/MS Liquid Chromatography Tandem Mass Spectrophotometry has been used to identify compounds in LPBE. The ADMET program is used to determine absorption profiles and bioavailability per oral. The tissue pharmacology approach uses Cytoscape 3.9.1, GeneCards, Disgenet, STRING 2.0.0, SRplot, and the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway to predict the molecular anti-cancer mechanisms of these compounds. In vitro validation using PyRx Autodock Vina 9.0 and Biovia Discovery Studio with BAX (PDB ID:2YXJ), BCL2 (P DB ID:2W3L) and STAT3 receptors (PDB ID:6NJS). A total of 17 active compounds were identified through LC-MS/MS. The moronic acid compound showed the highest levels of 14.29% followed by 4-Morpholineacetic Acid 12.2% and ursolic aldehyde 8.37%. Pharmacological network analysis showed that the compounder works on the EGFR tyrosine kinase resistance path by targeting the BCL2, BAX, STAT3 genes. The results of the in silico validation support the results of tissue pharmacology findings. Ursolic aldehyde, and Moronic acid showed a higher affinity to the three receptors. Therefore, Lansium parasiticum bark extract (LPBE) is recommended for further study as a candidate anti-cancer drug both in vitro and in vivo.